EXPLORING EVERYDAY URBAN ENVIRONMENT: AN INTERDISCIPLINARY IMMERSION INTO UNDERSTANDING CITIES - Puscasu, Ruxandra (European Scientific Journal, ESJ, 2014)
Similarly to other research fields in the arts and humanities, architecture stands for a complex phenomenon which gathers a wide range of ideas and philosophies, theories and actions. But, more than anything else, architecture is also an inherently interdisciplinary and multidisciplinary practice, and is also inextricably related to people’s everyday life. Therefore, higher education and research in the broad field of architecture and planning must learn how to deal with a wide spectrum of concerns, all of which can potentially impact directly on people’s lives or on their perception of the surroundings. Relying on scholars such as Repko (2008) this research focuses on investigations into the ‘lived’ dimension of the city, as a general concept to be addressed and further included in the architecture education and research. This understanding considers the city as a symbiosis of the physical layout and its experiential / ‘soft’ (Raban 1974) one and, therefore, picturing it as a whole can help one reach a more comprehensive understanding of its true character. Ultimately, it discusses the relevance of rethinking traditional approaches and strategies of investigating the city. In doing so, an alternative method of exploring urban reality is conceptualized.